Bovine Herpesvirus-4-Based Vector Delivering Peste des Petits Ruminants Virus Hemagglutinin ORF Induces both Neutralizing Antibodies and Cytotoxic T Cell Responses - Macchi, Francesca; Rojas, José Manuel; Verna, Andrea Elizabeth; Sevilla, Noemí; Franceschi, Valentina; Tebaldi, Giulia; Cavirani, Sandro; Martín, Verónica; Donofrio, Gaetano (Frontiers in Immunology, 2018)
Peste des Petits Ruminants Virus (PPRV) is an extremely infective morbillivirus that primarily affects goats and sheep. In underdeveloped countries where livestock are the main economical resource, PPRV causes considerable economic losses. Protective live attenuated vaccines are currently available but they induce antibody responses similar to those produced in PPRV naturally infected animals. Effective vaccines able to distinguish between vaccinated and naturally infected animals are required to PPRV control and eradication programs. Hemagglutinin (H) is a highly immunogenic PPRV envelope glycoprotein displaying both hemagglutinin and neuraminidase activities, playing a crucial role in virus attachment and penetration. In this study a recombinant Bovine Herpesvirus-4 (BoHV-4)-based vector delivering an optimized PPRV-Hemagglutinin expression cassette, BoHV-4-A-PPRV-H-ΔTK, was assessed in immunocompetent C57BL/6 mice. BoHV-4-A-PPRV-H-ΔTK-immunization elicited both cellular and humoral immune responses with specific T cell, cytotoxic T lymphocyte and sero-neutralizing antibody against PPRV. These data suggest recombinant BoHV-4-A-PPRV-H-ΔTK as an effective vaccine candidate to protect against PPRV herd infection and potentially applicable for eradication programs.